Breast and prostate cancer mortality and industrial pollution. (July 2016) - García-Pérez, Javier; Pérez-Abad, Natalia; Lope, Virginia; Castelló, Adela; Pollán, Marina; González-Sánchez, Mario; Valencia, José Luis; López-Abente, Gonzalo; Fernández-Navarro, Pablo
Abstract: We investigated whether there might be an excess of breast and prostate cancer mortality among the population residing near Spanish industries, according to different categories of industrial groups. An ecologic study was designed to examine breast and prostate cancer mortality at a municipal level (period 1997–2006). Population exposure to pollution was estimated by means of distance from town of residence to industrial facilities. Using Besag-York-Mollié regression models with Integrated Nested Laplace approximations for Bayesian inference, we assessed the relative risk of dying from these tumors in 2-, 3-, 4-, and 5-km zones around installations, and analyzed the effect of category of industrial group. For all sectors combined, no excess risk was detected. However, excess risk of breast cancer mortality (relative risk, 95% credible interval) was detected near mines (1.10, 1.00–1.21 at 4 km), ceramic industries (1.05, 1.00–1.09 at 5 km), and ship building (1.12, 1.00–1.26 at 5 km), and excess risk of prostate cancer was detected near aquaculture for all distances analyzed (from 2.42, 1.53–3.63 at 2 km to 1.63, 1.07–2.36 at 5 km). Our findings do not support that residing in the vicinity of pollutant industries as a whole (all industrial sectors combined) is a risk factor for breast and prostate cancer mortality. However, isolated statistical associations found in our study with respect to specific industrial groups warrant further investigation. Highlights: We studied breast and prostate cancer mortality near Spanish industries. Integrated nested Laplace approximations were used as a Bayesian inference tool. For all sectors combined, excess risk was not detected in any distance analyzed. Breast cancer risk was found near mines, ceramic industries, and ship building. Prostate cancer risk was found near aquaculture installations for all distances. Abstract : Isolated associations were found in our study between breast cancer and mines, ceramic industries, and ship building, and prostate cancer in relation to aquaculture installations.